Thickness‐dependent domain wall reorientation in 70/30 lead magnesium niobate‐ lead titanate thin films. Issue 9 (10th May 2017) - Keech, Ryan; Morandi, Carl; Wallace, Margeaux; Esteves, Giovanni; Denis, Lyndsey; Guerrier, Jonathon; Johnson‐Wilke, Raegan L.; Fancher, Chris M.; Jones, Jacob L.; Trolier‐McKinstry, Susan
Abstract: Continued reduction in length scales associated with many ferroelectric film‐based technologies is contingent on retaining the functional properties as the film thickness is reduced. Epitaxial and polycrystalline lead magnesium niobate‐lead titanate (70PMN‐30PT) thin films were studied over the thickness range of 100‐350 nm for the relative contributions to property thickness dependence from interfacial and grain‐boundary low permittivity layers. Epitaxial PMN‐PT films were grown on SrRuO3 /(001)SrTiO3, while polycrystalline films with {001}‐Lotgering factors >0.96 were grown on Pt/TiO2 /SiO2 /Si substrates via chemical solution deposition. Both film types exhibited similar relative permittivities of ~300 at high fields at all measured thicknesses with highly crystalline electrode/dielectric interfaces. These results, with the DC‐biased and temperature‐dependent dielectric characterization, suggest irreversible domain wall mobility is the major contributor to the overall dielectric response and its thickness dependence. In epitaxial films, the irreversible Rayleigh coefficients reduced 85% upon decreasing thickness from 350 to 100 nm. The temperature at which a peak in the relative permittivity is observed was the only measured small signal quantity which was more thickness‐dependent in polycrystalline than epitaxial films. This is attributed to the relaxor nature present in the films, potentially stabilized by defect concentrations, and/or chemical inhomogeneity. Finally, the effective interfacial layers are found to contribute to the measured thickness dependence in the longitudinal piezoelectric coefficient.